2015
DOI: 10.5562/cca2739
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Properties of Iron Oxide Nanoparticles in Shells of Hollow Microcapsules Designed for Biomedical Applications

Abstract: Abstract:The functional hollow biodegradable microcapsules modified with the maghemite γ-Fe2O3 nanoparticles and the hollow spherical CoFe2O4 / SiO2 nanocomposites were synthesized. Mössbauer spectroscopy data reveal that the main part maghemite nanoparticles have evident superparamagnetic behavior which is retained up to room temperature. This allows directing the microcapsules by an external magnetic field, which is very important for the problem of target drug delivery. On the other hand, the hollow spheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, one cannot exclude the formation of superparamagnetic ferric oxides during cathode preparation, which would contribute with a doublet overlapping with D1 signal from S1 sites. 37 To unveil this degeneracy, the spectra were acquired at 5 K, a temperature at which nano ferric-oxides contribute with a sextet component, 38,39 while the signal of S1 remains a doublet. 40 At 5 K, no sextet was visible for Fe0.5 while a sextet representing only 9 % of the absorption area, assigned to ferric oxide, appeared for Fe0.5cathode ( Figure S1c-d).…”
Section: Introductionmentioning
confidence: 99%
“…However, one cannot exclude the formation of superparamagnetic ferric oxides during cathode preparation, which would contribute with a doublet overlapping with D1 signal from S1 sites. 37 To unveil this degeneracy, the spectra were acquired at 5 K, a temperature at which nano ferric-oxides contribute with a sextet component, 38,39 while the signal of S1 remains a doublet. 40 At 5 K, no sextet was visible for Fe0.5 while a sextet representing only 9 % of the absorption area, assigned to ferric oxide, appeared for Fe0.5cathode ( Figure S1c-d).…”
Section: Introductionmentioning
confidence: 99%
“…The values of magnetic hyperfine fields (H ef f ) of these sextets depend not only on the differences in local surroundings of iron nuclei corresponding to them but also on magnetic crystal sizes. The value H ef f decreases when crystals pass to single-domain (superparamagnet) condition, in which magnet locking temperature depends on crystal size [53]. Moreover, the smaller the crystal size is, the lower the value H ef f is down to its full disappearance.…”
Section: Fig 3 Size Distribution Of Cofe 2 O 4 Crystallites Obtained By the Methods Of Microreactor Synthesis With Continuously Impingingmentioning
confidence: 99%
“…The near neighbor coordination of A site around B site is closer The direct line shape fitting of the measured spectra showed that all iron ions are in tetrahedral A-site and octahedral B-sites. A third more broadening sextet (C) reflected a magnetically-disordered structural state which was obviously-corresponded to iron ions on the surface of the NPs [74,75], in addition to one doublet (D).…”
Section: Mössbauer Spectroscopymentioning
confidence: 99%